Rabies-Related Knowledge, Attitudes, and Practices Among Primary School Students in Chonburi Province, Thailand - Mayurin Laorujisawat DVM, MPH; Aimutcha Wattanaburanon MSc, DEdu; Pajaree Abdullakasim MSc, PhD; Nipa Maharachpong MSc, PhD (SAGE Publishing, 2022)
In Thailand, rabies is an endemic fatal viral zoonosis where 40% of those infected are under age 15. The aim of this rabies KAP study (Knowledge, Attitudes, and Practices) is to examine preventive behaviors. A multistage sampling technique was employed for selecting the sample. Of 290 primary school students, 52.1% of them had poor knowledge, 89% had favorable attitudes, and 52.1% exercised proper preventive behaviors. We employed structural equation modeling to verify the systemic relationships and found rabies knowledge (β = .157, se=.059, P = .008) and attitude (β = .206 se=.054, P < .001) were associated with rabies preventive behaviors. Moreover, children in school No.4 statistically had less adept at rabies prevention than others. (β = - .232, se=.054, P < .001). This study highlights the need to strengthen rabies education programs, especially for rabies risk situations among school-aged children.